Child work and cognitive development: Results from four low to middle income countries. Issue 2 (25th May 2022) - Keane, Michael; Krutikova, Sonya; Neal, Timothy
Abstract : We study the impact of child work on cognitive development in four Low‐ and Middle‐Income Countries. We advance the literature by using cognitive test scores collected regardless of school attendance. We also address a key gap in the literature by controlling for children's complete time allocation budget. This allows us to estimate effects of different types of work, like chores and market/farm work, relative to specific alternative time‐uses, like school or study or play/leisure. Our results show child work is more detrimental to child development to the extent that it crowds out school/study time rather than leisure. We also show the adverse effect of time spent on domestic chores is similar to time spent on market and farm work, provided they both crowd out school/study time. Thus, policies to enhance child development should target a shift from all forms of work toward educational activities.